Self-supported MoS2@NHCF fiber-in-tube composites with tunable voids for efficient hydrogen evolution reaction - Zhu, Xiaobo (2020)
Molybdenum disulfide (MoS2) has emerged as an attractive noble-metal-free electrocatalyst for hydrogen evolution reaction (HER). However, the lack of active sites and low conductivity of MoS2 still remain challenging. Herein, we report a unique yolk-sheath structured nanocomposite consisting of MoS2 fiber core and nitrogen-doped hollow carbon fiber (NHCF) sheath (i.e. MoS2@NHCF), which is prepared by a simple electrospinning strategy combined with in-situ polymerization. Significantly, the well-defined internal void spaces within the MoS2@NHCF nanocomposite provide long range order and large specific surface area for rapid electrolyte diffusion and concentration. Besides, the NHCF sheath behaves as an effective conducting framework for fast electron transfer. Consequently, the hierarchically structured MoS2@NHCF nanocomposite demonstrates a low onset overpotential of 112 mV with a small Tafel slope (67 mV decade−1), being promising as an alternative high-performance HER electrocatalyst for the commercial platinum ones.